Pengembangan Literasi Membaca Siswa MI Melalui Pendekatan Kontekstual:: Studi Kualitatif - Muhamad Rizka Saomi; Muasromatul Azizah; Duladi AdiSodikin (Wulang: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to describe and analyze the development of reading literacy in elementary school (MI) students through the application of a contextual approach. The study focuses on the application of a contextual approach in reading instruction, the role of teachers in designing, implementing, and evaluating instruction, students' learning experiences, supporting and inhibiting factors, and its impact on students' interest, engagement, and reading comprehension. This study used a qualitative approach with a case study design. Data were obtained through observations of the learning process, in-depth interviews with teachers and students, and documentation studies of learning materials and the madrasah literacy program. Data analysis was conducted using an interactive model that included data reduction, data presentation, and conclusion drawing. The results indicate that the contextual approach was implemented through the selection of reading materials relevant to students' lives, linking text content to real life experiences, collaborative learning, utilizing the madrasah environment as a learning resource, and integrating Islamic values. Teachers acted as learning designers, facilitators, and reflective evaluators to ensure meaningful learning. Students experienced a positive learning experience, characterized by increased reading interest, active engagement, and reading comprehension. Supporting factors include teacher competence, student motivation, a literate environment, and family support, while limited resources and differences in student abilities pose obstacles. This study concludes that a contextual approach is effective in developing MI students' reading literacy holistically.